Hyaluronidase-induced matrix remodeling contributes to long-term synaptic changes - Sokolov, Rostislav; Krut', Viktoriya; Belousov, Vsevolod; Rozov, Andrey; Mukhina, Irina V. (Frontiers in Neural Circuits, 2025)
Extracellular brain space contains water, dissolved ions, and multiple other signaling molecules. The neural extracellular matrix (ECM) is also a significant component of the extracellular space. The ECM is synthesized by neurons, astrocytes, and other types of cells. Hyaluronan, a hyaluronic acid polymer, is a key component of the ECM. The functions of hyaluronan include barrier functions and signaling. In this article, we investigate physiological processes during the acute phase of enzymatic ECM removal. We found that hyaluronidase, an ECM removal agent, triggers simultaneous membrane depolarization and sharp calcium influx into neurons. Spontaneous action potential firing frequency increased rapidly after ECM destruction in interneurons, but not pyramidal neurons. Hyaluronidase-dependent calcium entry can be blocked by a selective antagonist of N-methyl-D-aspartate (NMDA) receptors, revealing these receptors as the main player in the observed phenomenon. Additionally, we demonstrate increased NMDA-dependent long-term potentiation at CA3-to-CA1 synapses during the acute phase of ECM removal. These findings suggest that hyaluronan is a significant synaptic player.